PENGARUH SELF-REWARD DAN DISIPLIN KERJA TERHADAP PENDAPATAN MITRA OJEK ONLINE DI JAKARTA TIMUR - Chaerudin, Iman; Astuti, Erlin Windiana; Lesmana, Yanto; Rustomo, Rustomo (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The main problem in Indonesia for decades has been that unemployment has been increasing every year. Online transportation seems to bring heaven to unemployed people of various ages and levels of education. This research aims to find the relationship and influence of self-reward and work discipline on online motorcycle taxi income. Recently, motorcycle taxi drivers have been stigmatized as a job that is considered trivial. The strength of self-control from various work pressures as an online motorcycle taxi means that drivers can indulge themselves in work but not forget to obey their partner's rules. Using quantitative methods, survey research used four shelters in the East Jakarta area as objects. By distributing questionnaires on a Likert scale to respondents met by chance, the data was declared valid and reliable, with the contribution of the two independent variables to the dependent variable being strongly positive and having a significant effect. Keywords: Self-Reward; Work Discipline; Income